2019
DOI: 10.3390/jcm9010110
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Renal Replacement Therapy (CRRT) in Children and the Specialized CRRT Team: A 14-Year Single-Center Study

Abstract: Continuous renal replacement therapy (CRRT) has been used as an important intervention in critically ill children. Our center has the only specialized CRRT team (SCT) for children in Korea, which consists of pediatric intensivists, a pediatric nephrologist and CRRT-specialized-nurses. This study was a retrospective single-center analysis, including all pediatric patients admitted to the intensive care unit (ICU) of Severance hospital in Korea and received CRRT between 2003 and 2016, grouped as before SCT (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A previous study has also linked reductions in intrinsic functional connectivity in the somatomotor network to participants with subclinical hypothyroidism compared to controls 27 . Interestingly, studies have also found subclinical thyroid dysfunction to be associated with sleep quality 28 , 29 . Other genes located in this intergenic region near PAX8 include CBWD2 and CHCHD5, which have also been associated with sleep duration in prior studies 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has also linked reductions in intrinsic functional connectivity in the somatomotor network to participants with subclinical hypothyroidism compared to controls 27 . Interestingly, studies have also found subclinical thyroid dysfunction to be associated with sleep quality 28 , 29 . Other genes located in this intergenic region near PAX8 include CBWD2 and CHCHD5, which have also been associated with sleep duration in prior studies 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In a large multicenter observational study, only 1.5% of critically ill children underwent CRRT (2). A knowledge gap exists regarding clinical and technical peculiarities of CRRT in the pediatric population (7), and several researchers in the field encourage the sharing of experiences and clinical and technical data (8)(9)(10)(11). Predictors for circuit clotting are mostly unknown and originate from large cohorts of adult patients (12,13).…”
Section: Introductionmentioning
confidence: 99%
“… 24 Single center, Turkey CRRT 2010–2015 50 42% at discharge Lee et al . 25 Single center, Korea CRRT 2003–2016 263 30% at discharge Tain et al . 26 Taiwan’s health care delivery system HD, PD, CRRT 2010–2017 412 6.59% of 23,759 encounters in 412 pediatric patients 66.4% at discharge Yetimakman et al .…”
mentioning
confidence: 99%